The Organizers’ Ecology: An Empirical Study of Foreign Banks in Shanghai - Kuilman, Jeroen; Li, Jiatao (Organization Science, 2006)
The organizing stages that predate entry into an organizational population were studied from an ecological perspective. Based on a detailed analysis of foreign banks in Shanghai, findings are presented that suggest that the likelihood of moving from the organizing phase to the operational stages is nonmonotonically dependent on the length of the waiting time. We found that firms seeking to gain entry into a population are negatively affected by the presence of other organizers in close geographical proximity, while the number of already-established organizations has an inverted U-shaped relationship with the aspirant’s likelihood of entering a relationship that operates more broadly. After investigating the effect of the geographical location of other potential entrants, as well as the effect of relative sizes and countries of origin, we have drawn inferences about the strength of these competitors’ identities and their impact on a social actor’s decision to enter the population. Our findings are informative not only for those studying organizational founding patterns, but also for those interested in the early process of identity formation.